Harvesting biogas from wastewater sludge and food waste - Chua K.H.; Cheah W.L.; Tan C.F.; Leong Y.P. (Institute of Physics Publishing, 2023)
Wastewater sludge and food waste are good source of biogas. Anaerobic treatment of slude and food waste able to produce biogas which is a potential renewable energy source. This study looks into the potential biogas generation and the effects of temperature on biogas generation. A lab scale reactor was used to simulate the biogas generation. The results show that wastewater sludge able to produced upto 44.82 ml biogas/kg of sludge. When mixed with food waste at a ratio of 30:70 (food waste), the biogas generated were 219.07 ml/kg of waste. Anaerobic of food waste alone produced biogas amount to 59.75 ml/kg of food waste. Anaerobic treatment also reduces the volume of waste. The effect of temperature shows that higher temperature produces more biogas than lower temperature. Published under licence by IOP Publishing Ltd.